1998
DOI: 10.1007/s001470050505
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of N-acetylcysteine as a hepatoprotective agent in liver transplantation

Abstract: One of the most common complications after liver transplantation is primary graft dysfunction which results from severe deterioration of the microcirculation. The data obtained from our experimental studies indicate that N-acetylcysteine (NAC) is able to reduce the severity of ischemia/reperfusion injury and improves postoperative graft function after liver transplantation in rats. The aim of this pilot study was to evaluate the efficacy of NAC as a hepatoprotective agent under clinical conditions. A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Multiple studies have shown partial protection to hepatic I/R using antioxidants (44), with variable clinical outcomes (45, 46). Complicating the picture, oxidative stress and inflammation are highly intertwined.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown partial protection to hepatic I/R using antioxidants (44), with variable clinical outcomes (45, 46). Complicating the picture, oxidative stress and inflammation are highly intertwined.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit models, intravenous NAC administration improved tissue oxygenation, microcirculation, alanine aminotransferase activity, and indocyanine green clearance [41]. Clinical trials of intravenous NAC have also had equivocal results, but three studies did document improved liver function, decreased liver injury, less graft dysfunction, less reject, and/or decreased hospital stay [13, 162, 175] (Table 3). …”
Section: Implication For Future Interventionsmentioning
confidence: 99%
“…Steib et al used higher maintenance doses of NAC but found no differences at all between the groups [7]. The most recently published study by Thies et al, however, demonstrated attenuated reperfusion injury as histologically graded, significantly increased flow in the portal vein, improved liver synthesis function, and prevention of primary graft non-function in NAC-treated liver graft recipients [6]. Since the dosing regimen of the two latter studies differs only in an additional rinsing of the graft with NAC containing solution (Thies et al), the divergence of the results may be attributable to the high interpatient variability in orthotopic liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, NAC has been evaluated as a hepatoprotective agent in clinical OLT and has shown favourable results in a recent study [6], whereas other studies did not demonstrate clinical benefit [7,8]. More detailed investigations with NAC treatment in OLT are needed [7].…”
Section: Introductionmentioning
confidence: 99%